A study protocol for an observational cohort investigating cardiac transthyretin amyloidosis flow reserve before and after Tafamidis treatment: The AMYTRE study - Vançon, Bastien; Bisson, Arnaud; Courtehoux, Maxime; Bernard, Anne; Bailly, Matthieu (Frontiers in Medicine, 2022)
Introduction: Anginal symptoms and signs of ischemia have been reported in some patients with cardiac transthyretin amyloidosis (ATTR) without obstructive epicardial coronary artery disease (CAD). Few studies found that coronary microvascular dysfunction was highly prevalent in subjects with cardiac amyloidosis, even in the absence of epicardial CAD. The purpose of this study is to confirm the coronary microvascular dysfunction, and to go further with evaluation of the effect of Tafamidis on microvascular dysfunction after 24 months of treatment. Methods and analysis: This study is a multicentric, prospective, observational cohort study. Adult patients with confirmed ATTR cardiomyopathy seen in the nuclear medicine departments of three large referral centers and treated with Tafamidis will be included. At baseline, patients will have a clinical and echocardiography evaluation. They will undergo a dynamic rest/stress dynamic cardiac scintigraphy with flow and reserve measurements before and 24 months after Tafamidis introduction. The primary outcome of this study will be the variation of stress and rest myocardial blood flow and flow reserve between baseline and 24 months after treatment. The effect of Tafamidis will be assessed by an intention to treat analysis. Ethics and dissemination: The study has received the following approvals: Orleans Hospital Research Committee (CHRO-2021-05) and Sud-Mediterranée IV Regional Ethics Committee (21 06 02). Results will be made available to physicians, the funders, and other researchers. Trial registration number NCT05103943.